Inovasi Kebijakan Pemerintah Daerah DIY dalam Membangun Ketahanan Pangan di Era Pandemi Covid-19 - Zarita Wattimena; Murni Septiyanti; Dyah Mutiarin (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2021)
The purpose of this research is to analyze policy innovations of the local government of Yogyakarta Special Region Province in improving people’s food security in the current pandemic era. DIY province is one of the areas affected by the spread of the Corona virus. Although this province does not include in areas with a high number of confirmed Covid-19 patients, the big impact experienced by DIY Province is because most of the sources of local and community income are from tourism industry. This affects the economic security and food security of the community where the community’s economy is declining which causes food security to be disrupted. The paradigm shift of public administration towards agile government requires the government to quickly and carefully develop public policy innovations to save the public from the impact of the ongoing pandemic. Researchers used interview methods and Secondary Data Analysis methods, namely data collection through research from various types of documents such as news, journals, books, papers and so on. Data in the form of interviews and various journals, news and related articles will be processed with Nvivo software to make data presentation more effective and efficient. The results of this study indicate that the food security sub-system most affected in DIY Province is the consumption sector. The important actor in implementing the DIY Province’s resilience policy innovation is the regional government through the DIY Provincial DPKP which has made their respective innovations in the fields of production, consumption and distribution of foodstuffs.